Investigating freezing-induced acidity changes in citrate buffers - Susrisweta, Behera; Veselý, Lukáš; Štůsek, Radim; Hauptmann, Astrid; Loerting, Thomas; Heger, Dominik (International journal of pharmaceutics, 2023)
Citrate buffers are commonly utilized in the field of biomolecule stabilization. We investigate their applicability in the frozen state within a range of initial pHs (2.5 to 8.0) and concentrations (0.02 to 0.60 M). Citrate buffer solutions subjected to various cooling and heating temperatures are examined in terms of the freezing-induced acidity changes, revealing that citrate buffers acidify upon cooling. The acidity is assessed with sulfonephthalein molecular probes frozen in the samples. Optical cryomicroscopy combined with differential scanning calorimetry was employed to investigate the causes of the observed acidity changes. The buffers partly crystallize and partly vitrify in the ice matrix; these processes influence the resulting pH and allow designing the optimal storage temperatures in the frozen state. The freezing-induced acidification apparently depends on the buffer concentration; at each pH, we suggest pertinent concentration, at which freezing causes minimal acidification.
Keywords: Buffers; koncentrace vodíkových iontů; citráty; zmrazování; Calorimetry, Differential Scanning; pufry; Freezing; Hydrogen-Ion Concentration; lyofilizace; Freeze Drying; Citrates; diferenciální skenovací kalorimetrie